Security and Sustainable Development in Africa: What Role for AFRICOM in the Continent - Aty, Mourad (Africana Studia, 2023)
Since the adoption of the 2030 Agenda for sustainable development, the United Nations has been actively disseminating seventeen (17) sustainable development goals (SDGs). The agenda calls for global partnerships for what it called “peace and prosperity for people and the planet”. SDG number sixteen (16) seeks to promote peace, justice and institutional efficiency. This seems to be a long and complex process when it comes to Africa. The African continent is the most fragile in terms of sustainable development given that most of its regions are conflict-torn. When it comes to peace and stability as a prerequisite to sustainable development, it is clear that the northern, western, and Horn regions are now the most unstable in the whole continent. Amidst all this, the United States Africa Command was created in 2007 to safeguard peace, bring stability and provide prosperity in the region. Drawing on source materials, mainly from the US Department of Defense and its Africa Center for Strategic Studies (ACSS), along with the AFRICOM Posture Statements to Congress of 2018 through 2022, this paper argues that the creation of the US Africa Command did not achieve any of the set mission goals. To the contrary, it was an attraction factor to terrorist groups which spread all over the region. Through several datasets, the paper also shows that more threats became imminent and more countries were plunged into bloodshed. More failed states in the region would make it impossible for the implementation of any of the 2030 Agenda’s SDGs. Keywords: Africa, AFRICOM, sustainable development goals, terrorism.